From Failed Human to Failed Man: A Gendered Analysis of Childhood Sexual Trauma in Osamu Dazai’s No Longer Human and Eka Kurniawan’s Seperti Dendam, Rindu Harus Dibayar Tuntas - Anna Anganita Theresia Latumeten; Dwinda Tamara (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study examines the representation of childhood sexual trauma and its impact on male subjectivity in Osamu Dazai’s No Longer Human and Eka Kurniawan’s Seperti Dendam, Rindu Harus Dibayar Tuntas. Employing a descriptive qualitative method and a comparative literary approach, the study analyzes how trauma is experienced, narrated, and mediated through gendered expectations of masculinity. The analysis draws upon trauma theory, particularly the works of Caruth and Herman, alongside theories of masculinity and gender proposed by Connell, Butler, and hooks. The findings reveal that both protagonists experience childhood sexual trauma that produces emotional silence, difficulties articulating vulnerability, and long-term psychological dysfunction. However, the consequences of trauma diverge significantly. Yōzō internalizes trauma through alienation, self-erasure, and withdrawal from human relationships, ultimately experiencing a collapse of human identity that positions him as a “Failed Human.” In contrast, Ajo Kawir externalizes trauma through violence, emotional displacement, and an obsessive concern with sexual capability, resulting in a crisis of masculine legitimacy that constructs him as a “Failed Man.” The study argues that trauma alone does not determine subjective outcomes; rather, masculinity mediates how trauma is understood, expressed, and embodied. By bringing together trauma studies and gender theory, this research contributes to existing scholarship by demonstrating how similar traumatic experiences can produce different forms of failure through the influence of gendered expectations and constructions of manhood.